Desarrollo de un intercambiador de calor compacto con esponjas metálicas - Morera-Alfaro, Moises (2025)
This paper describes a research work carried out to experimentally study a compact heat exchanger manufactured by 3D printing. The thermal device used metal sponges to increase the surface available for the heat transfer process. By studying several work conditions and different device configurations we obtained valuable experimental data to improve the energy transfer in the system.